Preventing Obesity in Canada’s Aboriginal Children: Not Just a Matter of Eating Right and Getting Active - Ferris, Melanie A (International Indigenous Policy Journal, 2011)
Obesity is a growing issue for all children. Many experts say that preventing obesity is largely a matter of eating the right foods and getting enough physical activity. This advice doesn’t recognize the fact that First Nations, Inuit, and Métis children face unique barriers to growing up healthy and strong simply because of their identity. This paper discusses how the social determinants of health impact the ability of Aboriginal children to grow up free of obesity. The paper highlights results from a community-based research project conducted amongst Aboriginal parents and service providers in Ontario who wish to prevent obesity amongst their own young children and clients. Research was carried out over two years to help develop a “toolkit” and training program to help service provides increase efforts to prevent obesity amongst First Nations, Inuit, and Métis children from the ages of 2 to 6 in Ontario.